Cambios en el estado nutricional del paciente quirúrgico coronario hospitalizado en el INCOR – EsSalud - Bustamante Carlín, María del Carmen (2012)
Aim: To compare the nutricional changes, by evaluating anthropometric and biochemical indicators, in heart disease patients that undergo open heart surgery at INCOR-EsSalud. Material and method: A descriptive prospective study was done in 92 heart patients with surgery indication that were taken care of at INCOR during the march – june period of 2011. Anthropometric and biochemical indicators were measured and key information from the medical history of each patient was taken into consideration. Results: Our total sample was 92 patients of which 60 (65,6%) were males and 32 (34,4%) were females. Hypertension was the highest comorbility found with 51 (54,8%) patientes being affected. The most common type of intervention was the CVC´s with 46 (49%) patients receiving this type of surgery. The weight, BMI and body composition indicators (skin folds) were measured in the pre and post stages of surgery. The results obtained for the pre stage were 69,0+14,5 for weight, 26+4,3 for the BMI, 28,6+3,6, 16,2+5,9, 23,5+3,2 for the skin folds, while the post surgery resultds were 66,1+14,5, 24,8+4,4, 26,8+3,4, 14,4+5,9, 22,3+3,1 respectevely, being lower in the latter. The same pattern was seen in the biochemical results where the values for hemoglobin, total count of lymphocytes (TCL) and albumin were lower in the post surgery stage than in the pre surgery stage; 12,7+1,8, 1911,0+651,1 and 4,0+0,5 for pre surgery and 10,3+1,3, 1749,3+734,3 and 3,3+0,4 for post surgery. We also found that the days of fasting and hospital stay were strongly related to the weight loss and nutritional deterioration in the patients. Conclusions: Heart surgery patients are exposed to nutritional changes mainly represented in weight loss and a drop in the biochemical indicators. Patients that undergo any type of surgery should recive adequate nutritional therapy, before and after the intervention, to ensure a better recovery with less weight loss and altereations in the body´s composition.